Implementasi Penyertaan Akad Wakalah Dalam Pembiayaan Murabahah Pada PT. Bank Syariah Indonesia, Tbk KCP Pangkalan Brandan - Maulana Azizi Rahman; Ahmad Sanusi Luqman; Anida M (Yayasan Rahmat Islamiyah, 2022)
This study focuses on the discussion of the process and realization of the distribution of murabahah financing, the inclusion of wakalah contracts in murabahah financing, and the economic perspective on the inclusion of wakalah contracts in murabahah financing by PT. BSI, Tbk KCP Pangkalan Brandan. The research method used in this study is a descriptive qualitative research method with an empirical approach. In this study, researchers used a collection technique, namely by means of observation, interviews, and documentation. Data processing and analysis techniques are data editing, data classification, data verification and drawing conclusions. The results of the study explain that the process and realization of murabahah contract financing at PT. BSI, Tbk KCP Pangkalan Brandan is almost the same as financing in general, starting with an application, survey and disbursement, while financing products using a murabahah contract are motor financing, car purchases, electronic goods purchases, raw material purchases, and home renovations. . Wakalah contract participation is carried out at the same time as the implementation of murabahah financing. The inclusion of wakalah contracts in murabahah financing by PT. BSI, Tbk KCP Pangkalan Brandan can be said to be illegal and not in accordance with Islamic economics, because in practice, the murabahah financing that has occurred has invalidated one of the pillars and conditions in buying and selling, namely the absence of goods being traded and the goods are not property rights. full of the contracting parties so that the delivery of the object cannot be carried out.